THE INFLUENCE OF TOXIC WORKPLACE ENVIRONMENT AND WORKLOAD ON TURNOVER INTENTION WITH WORK DISCIPLINE AS A MEDIATING VARIABLE AMONG GEN Z WORKERS IN THE HOSPITALITY INDUSTRY IN MALANG - Ayu Dewi Sartika; Ellisa Fadia Laili; Boge Triatmanto; Sunardi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study examines the impact of a toxic workplace environment and workload on turnover intention among Gen Z workers in the hospitality industry in Malang, with work discipline as a mediating variable. Using a quantitative approach, data were collected through surveys from 185 respondents selected via purposive sampling. The analysis employed linear regression and path analysis to explore relationships between variables. The findings indicate that a toxic workplace environment and workload significantly and positively affect turnover intention. Key factors contributing to employee turnover include interpersonal conflicts, poor leadership, excessive work hours, and task complexity. Additionally, these stressors negatively impact work discipline, reducing employees’ compliance and consistency. Work discipline partially mediates the relationship between a toxic workplace environment, workload, and turnover intention, as employees with high discipline are better equipped to manage work pressures and remain committed to the organization. This study supports the Job Demands-Resources theory and Herzberg’s motivation theory, emphasizing the role of personal resources in mitigating work-related stress. These findings provide practical implications for organizations to foster a supportive work environment, effectively manage workloads, and enhance employee discipline to reduce turnover rates in the hospitality industry.